THE IMPORTANCE OF PSYCHOLOGICAL DEPTH IN THE STORY’S ARTISTIC DESIGN (International Conference on Education, Psychology and Humanities, 2026)
The most terrible weapon of the 20th century is the desire to spread information and, in return, stay firmly in one's own land. There is talk that the countless animals being tested in biolaboratories may one day become the major cause of some plague or disease spreading on earth. The moon is a miracle of creation. These are evident in the mythological selection. In particular, a person can feel good about his life in the arms of new discoveries. In such a deep philosophical and psychological situation, it is not out of the question that a person is faced with countless problems. Mr. Cooper's steady pace in any matter of interest to know serves to ensure the sustainability of the creative concept in the architecture of the story. Therefore, many questions about existence become clear. The originality of the world, the diversity of thoughts and views, in the narrative of the new era, it is logically emphasized that there are many questions waiting to be solved before humanity, which is caught in the vortex of cosmogonic problems.
Keywords: Science fiction, psychological influence, space exploration, moon science, Arthur Clarke, artistic psychology.